2021
DOI: 10.1111/jce.15269
|View full text |Cite
|
Sign up to set email alerts
|

His‐Purkinje conduction system pacing: A systematic review and network meta‐analysis in bradycardia and conduction disorders

Abstract: Background His‐Purkinje conduction system pacing (HPCSP) has emerged as an effective alternative to overcome the limitations of right ventricular pacing (RVP) via physiological left ventricular activation, but there remains a paucity of comparative information for His bundle pacing (HBP) and left bundle branch pacing (LBBP). Methods A Bayesian random‐effects network analysis was conducted to compare the relative effects of HBP, LBBP, and RVP in patients with bradycardia and conduction disorders. PubMed, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“… 2 , 3 , 17 , 18 , 25 However, many publications reported much lower HBP implant success (63%–85%), especially in patients with left bundle branch block. 10 , 12 , 15 , 26 , 27 If CSP is to play a significant role in the world of pacing, it must be applicable outside highly specialized centers. In the present study, of the 10 cases in which no CSP could be established, 8 occurred in centers that had never tried LBBAP, and 1 case occurred in a center that had never tried HBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 , 17 , 18 , 25 However, many publications reported much lower HBP implant success (63%–85%), especially in patients with left bundle branch block. 10 , 12 , 15 , 26 , 27 If CSP is to play a significant role in the world of pacing, it must be applicable outside highly specialized centers. In the present study, of the 10 cases in which no CSP could be established, 8 occurred in centers that had never tried LBBAP, and 1 case occurred in a center that had never tried HBP.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Alternatively, pacing at the bundle of His or in the left bundle branch area directly stimulates parts of the cardiac conduction system and is collectively referred to as conduction system pacing (CSP). 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 CSP is attracting increasing attention because it maintains the physiological contraction pattern and better preserves the mechanical function of the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…Conduction system pacing, mainly utilizing His bundle pacing (HBP) and LBBAP, has been shown to achieve excellent electrical synchrony, and have the potential to prevent pacing-induced cardiomyopathy and the subsequent heart failure [19][20][21]. It is worth noticing that previous studies demonstrated a much higher feasibility of LBBAP than HBP in patients undergoing TAVI, characterized by higher success rate and lower pacing threshold [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have shown that HBP can produce favorable clinical outcomes in patients with CRT indications ( Shan et al, 2018 ; Qu et al, 2021 ). The HIS-SYNC trial showed that HBP resulted in a shorter QRSd and was equally effective in improving cardiac function, including LVEF and NYHA classification compared to CRT ( Upadhyay et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%